Students’ Effect in Using TikTok for Vocabulary Mastery and Students’ Interest in Learning English at an Islamic Secondary School - Arini Rusli; Andi Anto Patak; Nur Aeni (International Journal of Language, Education, and Literature, 2025)
This study examines how students at SMP IT As'adiyah Kaloling, a distant Islamic boarding school in Bantaeng, Indonesia, use TikTok in relation to their vocabulary knowledge and motivation in studying English. The study, which used a one-group pretest-posttest design and a quantitative technique, recruited 27 seventh-grade children. A vocabulary test, an interest survey, and structured interview questions were among the tools. With the mean score rising from 47.78 on the pretest to 86.67 on the posttest, the results showed a considerable improvement in the students' vocabulary mastery. This resulted in a normalized gain of 0.74, which was classified as high. With scores increasing from 37.63 to 44.89 and a normalized gain of 0.67 (medium-high category), students' engagement also improved. TikTok videos were used in the classroom for activities like sports and noun learning from @bluepopenglish. TikTok videos were used in the classroom for tasks like studying nouns from @bluepopenglish and sports vocabulary from @tinyme. All students considered TikTok-based learning to be more engaging and inspiring, according to structured interviews. The results are consistent with prior research that highlights TikTok's pedagogical potential for vocabulary learning and student engagement. This study's uniqueness is its rural setting, which demonstrates that, with teacher guidance, TikTok can be successfully included even in schools with little resources. TikTok showed to be an interesting tool that promotes vocabulary mastering and boosts students' enthusiasm and confidence in learning English, despite drawbacks such internet connection and the lack of a control group.